The importance of vowel diacritics for the temporary retention of high and low frequency Hebrew words of varying syllabic length. - Vaknin-Nusbaum, Vered; Miller, Paul (Memory & Cognition, 2011)
This study investigates the importance of vowel diacritics for the retention of Hebrew word lists, with word lists being manipulated along the dimension of word frequency and syllabic length. Eighty university students participated in the study. Half of the participants (40) were tested with the word lists presented in fully-pointed (voweled) Hebrew while the other half (40) were given the word lists in unpointed Hebrew (with vowel diacritics removed). Analyses of each group's recall rates and recall-order accuracy indicate that, overall, the presence of vowel diacritics had no facilitating effect on the participants' quantitative and qualitative Short Term Memory (STM) performance. This was found to be true whether word frequency (high vs. medium to low) or syllabic length (mono vs. trisyllabic) were computed as within-subject factors. Attempts to adequately interpret the absence of a pointing effect on STM performance based upon Orthographic Depth Hypothesis (ODH) and Grain Size Theory (GST) proved unfruitful. The authors propose an adaptation of the GST to the peculiarities of Hebrew orthography and discuss a morphology-centered grain-size theory (MGST).